Feasibility analysis of development of e-learning evaluation tool based on moodle on biology - Ariyanti Ariyanti; Hasanuddin Hasanuddin; Abdullah Abdullah (Jurnal Edubio Tropika, 2018)
The research aimed to find out the feasibility of e-learning evaluation tool based on Moodle on biology subject. This research had been conducted on April 2017 at SMPN 2 Banda Aceh. This research usedresearch and development method. The samples are 200 students of class VIII SMPN 2 Banda Aceh, consists of 8 classes, namely VIII-1, VIII-2, VIII-3, VIII-4, VIII-5, VIII-6, VIII-7, and VIII-8, and science teachers are 6 students. Data were collected using the questionnaire. The obtained data are responses of students and teachers on e-learning evaluation tool based on Moodle. The results showed that the validity test to e-learning evaluation tool based on Moodle has a validation rate of 87,5%. Response of students and teachers to e-learning evaluationtool based on Moodle is positive because the average of agree comments of students and teachers is ≥ 70%.Keywords: Development of Evaluation Tool, e-learning, Moodle and Biology